Programação e avaliação do ensino de leitura e escrita por meio de jogos educativos para crianças com dificuldades de aprendizagem - Tenório, Jacqueline Pimentel (2013)
A playful activity plays an important role in effective teaching, minimizing the appearance of aversive situations within the teaching situation, allowing the learning process to be more pleasant. Several instructional procedures are being developed, but few of these games are used as a tool. Thus, this study aimed to develop and evaluate the effectiveness of a procedure for teaching reading and writing grounded on the use of games. In this study were involved nine children aged between seven and 10 years, enrolled in initial ages of elementary education at a public school with teaching and learning difficulties in reading and writing. All participants were primarily exposed to an initial assessment of the repertoire written; relationship between figure-picture, picture-printed word, printed word, printed word and printed word, figure, and reading. The teaching program was composed of 13 training words of simple syllables of Brazilian Portuguese (consonant-vowel) and of six test words formed by recombination of syllables taught. The teaching procedure was divided into two units, both consisting of a board game involving selection activities of the figure on the model dictated word, naming figure, the selection of the printed word in front of the specimen is given, construction of the word before the word model printed, construction of the word before the model dictated word, and reading. The only difference between the units was the words employed. The criterion for passing from one unit to another was 100% correct reading of words in the post-training test drive. After each unit, a post-test composed of bingo games and crossword puzzles was applied to evaluate writing, relationship between dictated word-picture, dictated word-printed words and reading. Although nine participants were exposed to the initial evaluate repertoire, only four were exposed to the teaching unit I and two to teaching unit II. The results show gains in reading and writing repertoires of all participants exposed to the teaching procedure, especially in training words. After each unit, a post-test composed of bingo games and crossword puzzles was applied to evaluate writing, relationship between dictated word-picture, dictated word-printed words and reading. Although nine participants were exposed to the initial evaluate repertoire, only four were exposed to the teaching unit I and two to teaching unit II. The results show gains in reading and writing repertoires of all participants exposed to the teaching procedure, especially in training words. As conclusion, despite its efficiency, probably due to its innovative character, are required a number of modifications in this procedure so that future studies would present even better results for all participants.